Step by step synthesis of silver films by electroless technique and their SERS application of sodium arsenate - Quiroz, A. (2019)
In this work, we show the step by step synthesis of silver films using electroless technique. These films were obtained easily and economically in this job; which were used as SERS-active substrates. These substrates were characterized by atomic force microscopy, dark field microscopy, and SERS magnification. Rhodamine B, detection up to 1 ppb, was used as a test molecule for SERS magnification. These silver films were applied in the detection of sodium arsenate and with a detection limit of 100 ppb.